METHODS OF DEVELOPING CHILDREN’S PHYSICAL ACTIVITY (ON THE EXAMPLE OF PRESCHOOL EDUCATION) - Ganieva Vazira Yusufovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The physical education program provides a daily routine for each group. There are a variety of exercises available for children to perform the basic content of physical education on a regular basis. These are basic movements (walking, running, jumping, throwing, catching, crawling, sliding); general developmental exercises for the legs and body (with and without various objects) include dance exercises, purification and re-purification, movement games, mastering the essential features of various sports, sports exercises, roller skating, cycling, swimming, etc. finds.